2006
DOI: 10.1523/jneurosci.1203-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Late-Onset Leanness in Mice with Targeted Ablation of Melanin Concentrating Hormone Neurons

Abstract: The observation that loss of orexin (hypocretin) neurons causes human narcolepsy raises the possibility that other acquired disorders might also result from loss of hypothalamic neurons. To test this possibility for body weight, mice with selective loss of melanin concentrating hormone (MCH) neurons were generated. MCH was chosen to test because induced mutations of the MCH gene in mice cause hypophagia and leanness. Mice with ablation of MCH neurons were generated using toxin (ataxin-3)-mediated ablation stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
73
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(85 citation statements)
references
References 36 publications
9
73
1
Order By: Relevance
“…As it is unknown if the metabolic activity of WAT is altered in pmch Ϫ/Ϫ rats and as it has been demonstrated that WAT has a minimal contribution to EE (13), we chose to show EE not normalized, normalized for lean mass, and normalized for body weight. EE data normalized for body weight showed increased or a trend toward increased EE levels in pmch Ϫ/Ϫ rats compared with pmch ϩ/ϩ rats, which is in line with findings that oxygen consumption levels are increased in MCH Ϫ/Ϫ mice if normalized for body weight (1,59). However, EE not normalized or EE normalized for lean mass showed decreased or a trend toward decreased levels in pmch Ϫ/Ϫ rats compared with pmch ϩ/ϩ rats.…”
Section: E483supporting
confidence: 86%
See 2 more Smart Citations
“…As it is unknown if the metabolic activity of WAT is altered in pmch Ϫ/Ϫ rats and as it has been demonstrated that WAT has a minimal contribution to EE (13), we chose to show EE not normalized, normalized for lean mass, and normalized for body weight. EE data normalized for body weight showed increased or a trend toward increased EE levels in pmch Ϫ/Ϫ rats compared with pmch ϩ/ϩ rats, which is in line with findings that oxygen consumption levels are increased in MCH Ϫ/Ϫ mice if normalized for body weight (1,59). However, EE not normalized or EE normalized for lean mass showed decreased or a trend toward decreased levels in pmch Ϫ/Ϫ rats compared with pmch ϩ/ϩ rats.…”
Section: E483supporting
confidence: 86%
“…Relative Fto expression in pmch Ϫ/Ϫ rats was decreased at PND 40 and increased at PND 100 compared with pmch ϩ/ϩ rats, while relative expression of Pomc and Hcrt was normal at PND 40 but was decreased and increased, respectively, in pmch Ϫ/Ϫ rats compared with pmch ϩ/ϩ rats at PND 100. The expression profiles of Npy and Agrp in adult rats confirm findings in adult mice; however, the expression profiles of Pomc and Hcrt either partially agree or disagree with findings in adult mice (1,59). In summary, the time-related differences in expression profiles and a likely interaction between Pmch and the orexigenic and anorectic systems studied here could offer an explanation to the sudden stabilization of relative body weight but remain to be studied in more detail.…”
Section: E483supporting
confidence: 66%
See 1 more Smart Citation
“…Hypothalamic expression of MCH mRNA is upregulated during starvation in lean mice, as well as in genetically obese ob/ob mice (30), and MCH overexpression leads to obesity and to an increased susceptibility to high-fat feeding (19). In addition, acute or chronic intracerebroventricular administration of MCH or MCHR1 agonists stimulate feeding in rats and mice (11,15,30,32,36), while ablations of MCH (35,37), MCH neurons (2), and MCHR1 (9,21) have all been reported to promote fat loss mainly by increasing energy expenditure.…”
mentioning
confidence: 99%
“…The observations that mice with overexpression of MCH1-R are obese, MCH1-R knockout animals become lean and can develop a hypophagia [208,209] and leaness may occur also in consequence to ablation of melanin-concentrating hormone neurons [210] accelerated the efforts in search for suitable antagonistic agents up to date. Among these GW 856464 [211], AMG076 [212] and NGD-4715 [213] achieved phase 1 clinical investigations.…”
Section: Non-peptide Ligands Of Mch-receptorsmentioning
confidence: 99%